Pengembangan Objek 3D Memanfaatkan Piramida Hologram Berbasis Smartphone Materi Sistem Gerak Manusia - Ferdiansyah, Zaki Daffa; Kuswandi, Dedi; Soepriyanto, Yerry (Universitas Negeri Malang, 2022)
Research and development with the aim of producing a product in the form of a 3D object utilizing a smartphone-based hologram piramida of human movement system material. Research and Development (R&D) is research and development that refers to the Lee & Owen model with stages (analysis, design, development, implementation). With the application of 3D object media as a complement in science learning, media as a complement means that the media is applied to complement the material received by students in the classroom. The results of the product feasibility test that have been tested on media experts, material experts and students get a positive and feasible response. So it can be concluded that the 3D object media utilizes a smartphone-based hologram piramida, the human motion system material is suitable for use as a learning medium in the classroom, with the presence of 3D object media utilizing smartphone-based hologram piramidas can provide convenience in learning, motivate students to learn, display attractive media for students.AbstrakPenelitian dan pengembangan bertujuan menghasilkan produk berupa objek 3D memanfaatkan piramida hologram berbasis smartphone materi sistem gerak manusia. Research and Development (R&D) merupakan penelitian dan pengembangan yang mengacu pada model Lee & Owen dengan tahapan (analysis, design, development, implementation). Dengan penerapan media objek 3D sebagai pelengkap dalam pembelajaran IPA, media sebagai pelengkap berarti media diterapkan untuk melengkapi materi yang diterima siswa di dalam kelas. Hasil dari uji kelayakan produk yang telah diujikan kepada ahli media, ahli materi dan siswa mendapatkan respon positif dan layak. Sehingga dapat disimpulkan media objek 3D memanfaatkan piramida hologram berbasis smartphone materi sistem gerak manusia layak digunakan sebagai media pembelajaran di dalam kelas, dengan adanya media objek 3D memanfaatkan piramida hologram berbasis smartphone dapat memberikan kemudahan dalam pembelajaran, memotivasi siswa untuk belajar, menampilkan media yang menarik untuk siswa.